MITIGATING WATER DEFICIT IN COTTON CULTIVATION USING BACILLUS ARYABHATTAI - Rodrigues, Josiane Isabela da Silva; Zonta, João Henrique; Zonta, João Batista (Seven Editora, 2026)
Brazilian cotton production faces significant challenges due to water deficit, especially in second-crop cultivation in MATOPIBA. This study aimed to evaluate the effect of the bio-input Bacillus aryabhattai (Auras®) on germination, initial development, and tolerance to water stress in cotton. The research was conducted in two phases: the first evaluated the physiological quality of five cultivars (BRS 286, BRS 433 FL B2RF, BRS Rubi, BRS Jade, and BRS Verde) treated with five doses of the bio-input (0, 2, 4, 6, and 8 mL kg⁻¹). In the second phase, the BRS Jade cultivar, which showed the best initial performance, was subjected to full irrigation and water deficit regimes for seven days. The results showed that the dose of 2 mL kg⁻¹ was the most effective for root development in sand. Under water stress, plants treated with the bio-input, regardless of the dose, maintained height growth and biomass accumulation equivalent to plants under full irrigation, differing positively from the untreated control. It is concluded that B. aryabhattai acts as an efficient biostimulant and mitigator of water deficit, promoting greater physiological and morphological resilience in the initial phases of cotton cultivation.